The legal framework for alternative dispute resolution in courts with Shari'ah jurisdiction in Nigeria, Malaysia and Singapore - Oseni, Umar Aimhanosi (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2011)
Amicable resolution of disputes is a policy enshrined in the prime sources of Islamic law and this has been consistently practised in Muslim communities across the world since the advent of Islam. Therefore, the legal framework for ADR in Islamic law has a lot to offer in streamlining the modern practice of ADR. This study examines the legal framework for ADR in courts with Sharī'ah jurisdiction in Nigeria, Malaysia and Singapore. The major part of the study is dedicated to proposed reforms in the administration of justice system in the courts with Sharī'ah jurisdiction in Nigeria. Meanwhile, the Malaysian and Singaporean models of court-annexed ADR in the Sharī'ah court are closely studied with a view to proposing practical reforms for their Nigerian counterparts. The existing legal framework for ADR in courts with Sharī'ah jurisdiction in Nigeria is examined using qualitative legal research method. While 15 judges and other main stakeholders were interviewed, 145 Sharī'ah lawyers responded to the qualitative survey. The findings of this study reveal that the Sharī'ah Court of Appeal of two States in Nigeria (Kwara and Kogi States) have an informal dispute resolution mechanism, even though the existing legal framework setting up the court does not provide for court-annexed ADR. Over 95% of the respondents supported the proposed reforms in the administration of justice system. For the Malaysian and Singaporean aspects of the research, structured interviews were conducted. Pertaining to the practice of court-annexed ADR in the Sharī'ah courts in Malaysia, this study reveals that there is a need for more Sulh Officers in Malaysia to cater for the increasing number of cases. The Singapore Sharī'ah court should address the procedural challenges in its rules of evidence through the amendment of section 42 of the Administration of Muslim Law Act. Its decisions should not be subject to any modicum of supervision by the civil courts, as this will have some bearing on court-annexed mediation. In all, the findings of this research illustrate the adaptability of the practices in Malaysia and Singapore in the courts with Sharī'ah jurisdiction in Nigeria. The study is a significant contribution to the existing literature through the proposition of a Sharī'ah Court of Appeal (Sulh) Rules in Nigeria, which inculcates principles of amicable resolution of disputes into the formalised administration of justice system.